The Influence of the Socioscientific Issue Approach on the Problem Solving Skills of Class X Phase E Students - Rizqi Rohimah Lubis; Wahyuni Satria Dewi; Fatni Mufit; Rio Anshari (Postgraduate, University of Mataram, 2024)
The goal of 21 st century learning is to develop 4C skills in students. Problem solving is one part of the 4C skills that needs to be improved. Problem solving skills can be integrated to solve problems in the real world. In fact the level of problem solving skills of students at SMAN 3 Panyabungan is still relatively low. One solution that can be done to solve these problems is by using a socioscientific issue approach. The goal of this research is to specify the significant influence of the socioscientific issue approach on the problem solving skills of class X phase E students. This categorize of research is experimental research using a posttest only design and the sampling techniquei used was cluster random sampling. The population in this study was all class X phase E while, the sample was class X phase E1 as the experimentali class and class X phase E7 as the control class. Results obtained, the average value of the experimental class was higher than the control class, so that the value of th = 3.945 and the value of tt = 2.017 were obtained with a significance level of 0.05.